Bhutan [videorecording] in pursuit of gross national happiness - Griffiths, Steven; Salamon, Robert; Asian Development Bank. Information Office; Frontier Productions (Manila Asian Development Bank, 1997)
This video explores how Bhutan, which has been declared a role model in sustainable development, is balancing heritage and development.
Some interviews in Tibetan with English subtitles.
Interviews, Carola Molitor ; script, Steven Griffiths, Carola Molitor; on-line editing, Bobby Regalado ; Narration, Robert Salamon
Keywords: Sustainable development -- Bhutan; Bhutan -- Economic policy